Effect of oxygenation process on flux pinning in pristine and BaHfO3 nanocomposite GdBa2Cu3O7 superconducting thin films. (June 2020) - Popov, Ruslan; Ackermann, Kai; Rijckaert, H.; Hänisch, Jens; Van Driessche, I.; Holzapfel, Bernhard
Abstract: Pristine and BaHfO3 (BHO) nanocomposite GdBa2 Cu3 O7 (GdBCO) superconducting thin films were deposited at 800 °C, 0.4 mbar O2 partial pressure using a Nd:YAG laser (λ=355 nm) with 10 Hz frequency on MgO substrate. The influence of the oxygenation process on flux pinning and electrical transport properties was investigated by changing the annealing temperature ( T ann ) between 450 °C and 780 °C and the holding time ( t hold ) between 10 and 30 min. The irreversibility field shows the largest shift toward higher fields for T ann = 450 °C and thus the largest in-field J c . Angular dependence of J c for most of the pristine GdBCO films exhibits a large peak for B ‖ c, however the sample with T ann = 550 °C has a large peak in the 90°-120° region, i.e. near B ‖ ab . For BHO nanocomposites, a decrease in T ann increases in-field J c by a factor of 2.